2022
DOI: 10.3389/fpls.2022.998910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbon balance and carbohydrate reserves from forced (Vitis vinifera L.) cv. Tempranillo vines

Abstract: Elevated temperatures during berry ripening have been shown to affect grape quality. The crop forcing technique (summer pruning that ‘force’ the vine to start a new cycle) has been shown to improve berry quality by delaying the harvest date. However, yield is typically reduced on forced vines, which is attributed to vine low carbon availability soon after forcing and likely incomplete inflorescence formation. The present study aims to estimate the carbon balance of forced vines and evaluate vine responses to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
3
4
1
Order By: Relevance
“…We did not observe a reduction in the number of bunches per vine in F1 when compared to F2. This observation is contrary to other short-term (maximum 2-year trial) studies using similar forcing pruning dates, in which it was observed that the number of bunches per vine increased when forcing was carried out later [5,6,13]. No clear effects of the forcing date on the number of bunches per vine was observed in long-term studies [10].…”
Section: Vine Performance and Grape Quality Responses To Forcing Date...contrasting
confidence: 91%
See 4 more Smart Citations
“…We did not observe a reduction in the number of bunches per vine in F1 when compared to F2. This observation is contrary to other short-term (maximum 2-year trial) studies using similar forcing pruning dates, in which it was observed that the number of bunches per vine increased when forcing was carried out later [5,6,13]. No clear effects of the forcing date on the number of bunches per vine was observed in long-term studies [10].…”
Section: Vine Performance and Grape Quality Responses To Forcing Date...contrasting
confidence: 91%
“…This last observation is rather controversial. Contrary to our observations, some studies have reported that forced vines require more GDD to reach veraison than unforced vines [6,10], whereas studies realized in the same region as the present studies are in accordance with our results [7,13]. These contradictory results suggest that GDD should be taken with caution when comparing data from different climatic regions and with different irrigation strategies and when comparing unforced with forced vines, since other parameters besides temperature (including photoperiod, carbohydrate availability and periods of extreme high temperatures) may alter phenology [20].…”
Section: Weather Conditions and Phenologysupporting
confidence: 90%
See 3 more Smart Citations